2019
DOI: 10.1247/csf.19022
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in <i>mxc</i> Tumor-Suppressor Gene Induce Chromosome Instability in <i>Drosophila</i> Male Meiosis

Abstract: Drosophila Mxc protein is a component of the histone locus body (HLB), which is required for the expression of canonical histone genes, and severe mxc mutations generate tumors in larval hematopoietic tissues. A common characteristic of cancer cells is chromosomal instability (CIN), but whether mxc mutants exhibit this feature is unknown. Here, examination of post-meiotic spermatids created after male meiosis revealed that a fraction of the spermatids in hypomorphic mxc G46 mutants contained extra micronuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 63 publications
(98 reference statements)
0
14
0
Order By: Relevance
“…To judge whether two consecutive meiotic divisions were properly performed, we observed nuclei in post-meiotic spermatids under phase contrast microscopy, as previously described [36,37]. A pair of testes from pharate adults or newly eclosed adult flies (0-1 day old) were dissected to isolate spermatocyte cysts in Testis buffer (183 mM KCl, 47 mM NaCl, 10 mM EDTA, pH 6.8) and covered with 18 × 18 mm-coverslip (Matsunami, Osaka, Japan) to flatten the cysts.…”
Section: Preparation Of Onion Stage Spermatidsmentioning
confidence: 99%
See 1 more Smart Citation
“…To judge whether two consecutive meiotic divisions were properly performed, we observed nuclei in post-meiotic spermatids under phase contrast microscopy, as previously described [36,37]. A pair of testes from pharate adults or newly eclosed adult flies (0-1 day old) were dissected to isolate spermatocyte cysts in Testis buffer (183 mM KCl, 47 mM NaCl, 10 mM EDTA, pH 6.8) and covered with 18 × 18 mm-coverslip (Matsunami, Osaka, Japan) to flatten the cysts.…”
Section: Preparation Of Onion Stage Spermatidsmentioning
confidence: 99%
“…A pair of testes from pharate adults or newly eclosed adult flies (0-1 day old) were dissected to isolate spermatocyte cysts in Testis buffer (183 mM KCl, 47 mM NaCl, 10 mM EDTA, pH 6.8) and covered with 18 × 18 mm-coverslip (Matsunami, Osaka, Japan) to flatten the cysts. For observation of nuclear organization in onion stage spermatids, thecysts of spermatids collected from adult testes in Testis buffer supplemented with DAPI were mildly flattened under a cover slip, and phase contrast micrographs and fluorescence images were successively acquired [36,37]. To observe fixed spermatid samples, we removed the coverslips after freezing the slides, and transferred them into 100% methanol for 5 min.…”
Section: Preparation Of Onion Stage Spermatidsmentioning
confidence: 99%
“…We induced the ectopic expression of dsRNA against mxc mRNA in the three regions of LG, namely, CZ, MZ, and PSC, while using region-specific Gal4 drivers. The UAS-mxcRNAi HMS00444 used in this study can efficiently deplete endogenous mxc mRNA in the testes while using the testis-specific Gal4 driver [25]. In this study, we used the Hml-Gal4 driver to deplete the endogenous mRNA in CZ, the upd3-Gal4 driver to deplete it in MZ, and the col-Gal4 driver for depletion in PSC (for control see Figure 2a-c; for mxc depletion see Figure 2d-f).…”
Section: Depletion Of MXC In the Matured Hemocytes Of Lg Resulted In mentioning
confidence: 99%
“…Although the mechanism underlying the changes in histone gene expression has not yet been clarified, it can be interpreted, as follows; the alterations in the expression of the five histone mRNAs resulted in DNA replication stress and the accumulation of DNA damage [24,68]. However, another study showed that the mRNA levels of the five canonical histones were constantly reduced in the testes of the hypomorphic mutants for mxc [25]. In addition, DNA damage foci that were examined by immunostaining using anti-H2Av antibody were not evident in the mutant cells.…”
Section: Mature Hemocyte-specific Expression Of Polyadenylated Mrnas mentioning
confidence: 99%
See 1 more Smart Citation